2022
DOI: 10.1080/21645515.2022.2035141
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of adverse events following immunization of 13-valent pneumococcal conjugate vaccine among infants, in Zhejiang province, China

Abstract: Objectives To evaluate the safety of 13-valent pneumococcal conjugate vaccine (PCV13) after its licensure. Methods Review and describe the AEFI reported to national adverse event following immunization surveillance system (NAEFISS) in Zhejiang province from 2017 to 2020. Reporting rates of AEFI were calculated by age, city, severity of AEFI, categories of AEFI, and reaction categories. The data mining algorithm used in this study was reporting odds ratio (ROR). A value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 34 publications
(35 reference statements)
2
6
0
Order By: Relevance
“…CNAEFIS operates according to China’s national AEFI guidelines, which are supported by various laws, including the Law of the People’s Republic of China on the Prevention and Treatment of Infectious Diseases, Drug Administration Law of the People’s Republic of China, Vaccine Administration Law of the People’s Republic of China, National Immunization Program Operational Guidelines, Regulations on the Prevention and Response to Public Health Emergencies, and other laws and regulations [ 16 ]. The objectives of CNAEFIS include monitoring abnormal changes in known AEFIs, identifying potential risk factors, evaluating the safety of newly marketed vaccines, and providing evidence to improve vaccine quality and vaccination services [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…CNAEFIS operates according to China’s national AEFI guidelines, which are supported by various laws, including the Law of the People’s Republic of China on the Prevention and Treatment of Infectious Diseases, Drug Administration Law of the People’s Republic of China, Vaccine Administration Law of the People’s Republic of China, National Immunization Program Operational Guidelines, Regulations on the Prevention and Response to Public Health Emergencies, and other laws and regulations [ 16 ]. The objectives of CNAEFIS include monitoring abnormal changes in known AEFIs, identifying potential risk factors, evaluating the safety of newly marketed vaccines, and providing evidence to improve vaccine quality and vaccination services [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Non-severe AEFIs included those that either required no intervention or may have necessitated medical consultations and led to minor disruption of daily activities or loss of work time. In contrast, serious AEFIs were described as adverse health episodes that had significant clinical repercussions, such as fatality occurrences, patient hospitalization, extended stays in healthcare settings, sustained or major disabilities or functional limitations, life-threatening conditions, or the appearance of congenital disorders [ 14 , 16 ]. In China, we assembled groups of AEFI experts to evaluate the causal relationships of cases and classify them according to the WHO manual.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The national AEFI surveillance system (NAEFISS), which is a passively collected spontaneous electronic database, has been in operation since 2005. 7 Although the reporting sensitivity has improved from 9.2/100,000 doses for the time period of 2008–2011 to 56.64/100,000 doses in 2019 in Zhejiang province, 8 the reporting rate of AEFI detected through the passive surveillance system is likely to be lower than the true rate, due to the bias of under-reporting. A previous study indicated that the role of healthcare workers (HCWs), who interacted with persons experiencing adverse events, was indisputable in initiating the reporting and investigation process.…”
Section: Introductionmentioning
confidence: 99%